Electricity supply to agriculture in Andhra Pradesh and Punjab: An overview - Birner, Regina; Sharma, Neeru (International Food Policy Research Institute, 2011)
Whereas in India fertilizer policy is the responsibility of the federal government, electricity policy is a joint responsibility of the central government and the states. This chapter provides an overview of the two states that have been selected for the empirical analysis of electricity supply to agriculture: Andhra Pradesh and Punjab.